Effect of mindfulness group therapy on maternal psychological distress and perinatal outcomes in twin pregnancy: a randomized controlled trial - Zhou, Ying; Tang, Zai-Mei; Mei, Lin; Yang, Xiao-Chang; Zheng, Hong-Ling; Liao, Bi-Zhen; Yu, Xin-Yang (Frontiers in Psychiatry, 2025)
PurposePsychosocial stress, depression, and anxiety are prevalent during pregnancy and can be associated with adverse birth outcomes. This study aimed to evaluate the effectiveness of an online Mindfulness Group Therapy (MGT) program in improving perinatal maternal psychological distress and perinatal outcomes among women with twin pregnancies.MethodsIn this randomized controlled trial, 120 women carrying twins were assigned to MGT groups (6-week, 120 minutes of mindfulness intervention weekly) or control groups (usual perinatal care and health education). The primary outcomes were maternal psychological distress, including depression, anxiety, stress, and mindfulness measured by the Edinburgh Postnatal Depression Scale, State Anxiety Inventory, Perceived Stress Scale, and Five Facet Mindfulness Questionnaire at three points: baseline, post-intervention and time one month postpartum. Secondary outcomes included maternal pregnancy outcomes and neonatal outcomes.ResultsA total of 109 women with twin pregnancies completed the intervention. The intervention significantly and effectively prevented the worsening of postpartum depression symptoms in women with twin pregnancies, improved mindfulness, and reduced perceived stress (P < 0.05). Significant differences were observed at both post-intervention, and 1-month post-delivery (P < 0.05). However, no significant differences were found in anxiety scores (P > 0.05). Intention-to-treat analysis further revealed that the intervention had a significant effect on reducing postpartum depressive symptoms (P < 0.05), even when considering participants who did not complete the entire study process. In terms of pregnancy outcomes, a significant difference was found between the intervention and control groups in the incidence of low birth weight (P<0.05).ConclusionMGT proves potentially effective in reducing perinatal stress, preventing prenatal depression, and decreasing the incidence of low-birth-weight infants in twin pregnancies. These findings support the integration of group mindfulness interventions into prenatal mental health care to mitigate prenatal depression among women expecting twins.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=131787, identifier ChiCTR2100050091.